FAKTOR-FAKTOR EFEKTIVITAS SISTEM E-AUDIT (STUDI EMPIRIK PADA E-AUDIT PERJALANAN DINAS BPK RI PERWAKILAN PROVINSI JAWA TENGAH) - Dewi Nindyastuti; Endang Kiswara (Diponegoro Journal of Accounting, 2014)
This study aims to examine the factors the effectiveness of e-audit system in the BPK RI Representative of Central Java province. The variables associated with the effectiveness of e-audit system, such as the competence of the examiner, the audit findings, perceived ease, perceived usefulness, quality systems, and quality information. This study was conducted with non-probability method through a case study with a population of respondents is representative examiner BPK which has implemented the e-audit as many as 17 people. Tests were conducted in the study using SPSS 19 with the type of non -parametric tests such as the Shapiro Wilk normality test, and hypothesis testing with Pearson Product Moment correlation test.The results showed that there is a positive and significant relationship between the variables of audit findings, perceived ease of use, perceived usefulness, system quality, information quality and effectiveness of e-audit system.